Formulation and In Vitro Evaluation of Oral Capsules from Liquid Herbal Antimalarials Marketed in Ghana - Christina Osei-Asare; Fredrick William Akuffo Owusu; Philomena Entsie; Ama Kwansima Annan; Rita Akosua Gyamaa; Edem Makafui Amenuke (Journal of Tropical Medicine)
Malaria ranks amongst the major health challenges faced by many developing countries. In Sub-Saharan and tropical regions of Africa, malaria continues to claim the life of one out of every twenty children below the age of five years. In adults, mortality rates are lower, but frequent debilitating attacks reduce the quality of life for chronic sufferers. The patronage and usage of liquid herbal antimalarials in the management and treatment of malaria in Ghana have been on the ascendency over the past decade. This project seeks to transform five liquid herbal antimalarial preparations (Agbeve pevah, Time mixture, Givers mixture, Masada mixture, and Rooter mixture) produced locally and commonly used for the treatment of malaria fever into capsules. This will help eliminate the current limitations, such as lack of patient compliance due to the bitterness and bulky nature of packaged preparation. The amount of dry extract per dose of each herbal antimalarial preparation and the wavelength of maximum absorption (λmax) of aqueous solutions of Agbeve, Time, Givers, Masada, and Rooter extract were determined. The flow properties of formulated granules were determined and subsequently encapsulated. The formulated capsules were evaluated using basic pharmacopeial tests, such as uniformity of weight, disintegration, drug content, and dissolution. Difference, f1, and similarity, f2, factors were employed in analyzing the dissolution profiles of the formulated capsules. The formulated granules exhibited good flow properties and passed the weight uniformity, disintegration, and drug content tests. The capsules exhibited optimal release of extract at the 45th minute in 0.1 M HCL. All formulated capsules had ƒ2 values >50 and ƒ1 values <15, indicating the similarity of their drug release profiles with their respective liquid herbal antimalarials. Oral capsules of Agbeve, Time, Givers, Masada, and Rooter have been successfully formulated and can be used as a substitute for Agbeve pevah, Time mixture, Givers mixture, Masada mixture, and Rooter mixture, respectively, in the treatment of malaria.